Management of Tumors of the Ischiorectal Fossa. Issue 10 (October 2015) - Buchs, Nicolas C.; Mortensen, Neil J.; Guy, Richard J.; Gibbons, Max; George, Bruce D.
<x xml:space="preserve">Abstract</x> BACKGROUND: Noninflammatory masses in the ischiorectal fossa are rare. OBJECTIVE: This study aimed to review our experience with ischiorectal fossa tumors and to address the question of whether percutaneous biopsy should be undertaken. DESIGN: This is a retrospective study. SETTINGS: This study was conducted at a tertiary institution. PATIENTS: From April 2007 to November 2014, all consecutive ischiorectal fossa masses treated in a referral center were retrospectively reviewed. They were all presented and discussed in a multidisciplinary team meeting. Magnetic resonance imaging was performed in all the patients. Inflammatory pathologies, such as abscess, were excluded from the analysis. INTERVENTIONS: Percutaneous biopsy and surgical excision of ischiorectal fossa tumors were reviewed. MAIN OUTCOME MEASURES: Perioperative, pathological, and oncological outcomes were measured. RESULTS: Eleven patients were identified (8 female; median age, 50 years; range, 25–90). Percutaneous biopsy was undertaken in 8 patients. All biopsies were diagnostic and altered preoperative management in 3 cases (aggressive angiomyxoma (n = 2), desmoid fibromatosis (n = 1)). Overall final diagnosis was benign in 3 patients, locally aggressive neoplasm in 3, and malignant in 5 cases (leiomyosarcomas (n = 2), liposarcomas (n = 2), and angiomyosarcoma (n = 1)). Surgical approaches were perineal in 8 patients, abdominoperineal in 1 patient, and totally abdominal in 1 patient. One patient (age 90 years) was managed nonsurgically. After resection, 2 positive margins were observed (R1 rate, 20%). After a mean follow-up of 24.3 months, 3 patients have experienced local recurrence, which required further surgery in 2 cases. LIMITATIONS: This study is limited by the small number of patients. CONCLUSIONS: Noninflammatory masses in the ischiorectal fossa are rare, but they are commonly malignant and should be imaged by MRI. Unless the radiological appearances are diagnostic, percutaneous biopsy is recommended and alters management in about one-third of cases.